LEGAL REGULATIONS OF SUPPORT OF UKRAINIAN REFUGEES BY STATE AUTHORITIES AND LOCAL SELF-GOVERNMENT IN THE REPUBLIC OF POLAND - Matviichuk Оlena; Ryzhenko Іgor (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Aim: to study the peculiarities of the legal regulation of support of Ukrainian refugees by polish public administration institutions, which leads to (1) the definition of legislative acts that are the basis of such regulations and (2) the specifics of the practical application of these acts. To achieve this goal, the provisions of Polish national legislation are analysed, as well as analytical and normative materials devoted to various aspects of support of Ukrainian refugees by Polish public administration institutions. Research methods: general, theoretical and analytical methods were used in combination with an comprehensive approach. Results: at theoretical level, the study found that the substantive approach of the Polish government to the organization of support to Ukrainian refugees from Russian aggression is based on a system of international and national legislative acts in the field of humanitarian law. The adoption by the Polish parliament of a special law «On assistance to the citizens of Ukraine in connection with the armed conflict on the territory of that state» allowed to regulate legal relations arising from the extraordinary influx of Ukrainian refugees in a short period of time. It is shown that the norms of the mentioned law regulate the actions of both organizational and legal institutions at the level of state power and local self-government. A fundamental precondition for this state of affairs in the field of refugee issues is the well-thought-out use by the Polish authorities of the tools of normative-legal construction of the public administration’s legal basis. Discussion: for Ukraine, in a situation of russian aggression, the issue of organizing and providing social assistance to refugees – internally displaced individuals, is extremely important. The analysis of the experience of the Polish state is useful in terms of improvement of interaction between public authorities, local self-governments and non-governmental organisations (volunteer organisations). Polish authorities showed an integrated approach to the issues of (1) legal residence of refugees in Poland, (2) providing opportunities for employment and business growth, (3) access to various social benefits.